Dynamics of growing of Russian sturgeon (Acipenser gueldenstaedtii) larvae for different durations of cultivation - V. O. Kornienko; V. V. Olifirenko (Regulatory Mechanisms in Biosystems, 2020)
In the context of the need to preserve the biodiversity of natural waters, the cultivation of valuable fish species for stocking natural reservoirs takes on exceptional importance. Optimization of the technology for growing sturgeon in artificial conditions has become the main goal of our research. The population used for the present study is from a fish farm, Dneprovskiy Sturgeon Fish Breeding Factory located in Belozersky district (Kherson region, Ukraine). Studies were conducted for ten years (2007–2017). The objective of our study is to assess the quality of juvenile sturgeon when grown with different durations. The research material was provided by the free embryos and larvae of Russian sturgeon (Acipenser gueldenstaedtii von Brandt & Ratzeburg, 1833). Formation of experimental groups and calculation was performed on the principle of groups-analogues by standard methods. The main resultant criteria were larval survival, optimal extrinsic performance, and fish productivity. As a result of the conducted research it was determined that the optimal term of growing the larvae of A. gueldenstaedtii in the pools was 20 days. During this period, young sturgeon had high rates of average body weight with a survival rate of at least 53.4–60.2% and optimal physiological state. In variants with a maximum growth period of 24 days, the difference in the individual masses of the test material was significantly increased on the background of rather high mass indices of the larvae (1.2–1.4 and 1.9–2.1 times, respectively for II–III variant). This led to an increase in the pressure of food competition and, as a result, to a decrease in the output of young sturgeon growth of up to 46.5–61.9%. Survival of the larvae was by far the highest in the experimental groups with a minimum period of cultivation and ranged within 75.1–80.7%. The maximum level of fish productivity was observed in the third variant of the experiment with the longest period of cultivation. An analysis of the relative indicators of body weight gain revealed that with the extension of the growing period in experimental variants the percentage of realization of growth of larvae during the period of exogenous feeding was proportionally reduced. The most effective use of feed for the growth of body weight of the larva was in the variant with a growing period of 20 days. Feed costs in these groups ranged within 2.80–3.24, which averaged 2.83–3.02. Analysis of the dynamics of oscillations of the main biochemical indicators showed that the accumulation of consumables in the body of the experimental larvae increased with the growing period of cultivation in the pools. The amount of moisture was adequately reduced. The greatest influence on the results of the growth of sturgeon larvae in the pools among all the considered factors belonged to the period of cultivation, the magnitude of significance of which was 61.2%. The research results should significantly improve the technology of growing the Dnieper population of A. gueldenstaedtii on fish farms.